Knowledge of Cervical Cancer and Utilization of Screening Services among Female Nurses in Federal Medical Center Owerri, Imo State, Nigeria - Nwabueze A.E; Ezeama M.C (Poltekkes Kemenkes Yogyakarta, 2021)
Cervical cancer is a scourge among women but female nurses are not paying attention to this menace. This study set out to determine the knowledge of cervical cancer and utilization of cervical cancer services among female nurses in Federal Medical Center Owerri, Imo state, Nigeria. Five objectives were set to guide the study. Descriptive survey design was adopted. Target population was the 820 female nurses working at the centre at the time of the study. Sample size of 326 was statistically determined using Taro Yamen formula. Sampling technique used was stratified and random sampling technique. Instrument of data collection was a pretested self-administered structured questionnaire. Data was analyzed using descriptive statistics of frequencies, percentages, bar and pie charts. Hypothesis was tested using inferential statistics of Pearson Chi-square and Statistical Package for Social Sciences (SPSS) 21.0 version at P-value of 0.005 level of significance (p<0.05). The result showed that awareness of screening services 315 (96.6%) and knowledge of cervical cancer 283(86.8%) are adequate but the utilization of screening services is very poor 94 (29%). There was statistical association between knowledge of cervical cancer, availability of screening services(p<0.05) and utilization of cervical screening services but no significant statistical association with Age, Educational level and Religious affiliation(p>0.05).Fear of result 90(38.8%) and lack of time 60(25.9%) ranked high among others in the factors militating against utilization of cervical cancer screening. Recommendations were made that hospital management and allied educators should organize and re-invigorate enlightenment programs to allay the fears of the nurses and step it down to colleges/schools of nursing in a bid to keep this preventable scourge in check among nurses which will dove-tail to the community.